Development of parallel and fan-shaped beam mixed-projection optical tomography - Mohd. Muji, Siti Zarina (2012)
Parallel and fan shaped beam are two common projections that had been used widely in optical tomography system. These projections never have been merged before in the process of tomography area. In this paper, some enhancement has been made by combining these two modalities in order to solve the ambiguity that arises in the parallel beam projection.